Maladaptive personality traits as predictors of prosocial and trusting behavior in two economic games - Hepp, Johanna; Mohr, Melissa; Niedtfeld, Inga (Borderline Personality Disorder and Emotion Dysregulation, 2022)
Dimensional models of personality disorders postulate interpersonal dysfunction as the core feature of personality pathology, and describe maladaptive personality traits that characterize the specific pattern of dysfunction that is experienced. Herein, we examined whether maladaptive traits predict prosocial and trusting behavior, both of which are highly relevant behaviors for interpersonal functioning. Specifically, we examined antagonism as a predictor of prosocial behavior in a dictator game, and suspiciousness as a predictor of trust in the faith game.